DECONTEXTUALIZING THE DIVINE: ETHICAL CONCERNS IN THE COMMODIFICATION OF DHOKRA DEITIES. - Patel , Aditi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The appropriation of Indigenous art by elite designers and visual artists in India has raised significant ethical concerns in contemporary discourse. Indigenous art forms, deeply rooted in the cultural and spiritual traditions of India’s tribal communities, are increasingly integrated into mainstream design and visual arts without proper acknowledgment, consent, or fair compensation. This practice often results in the erosion of the cultural context and significance of these artworks, reducing sacred and symbolic expressions to aesthetic commodities in high fashion, home decor, and commercial visual art. The ethical concerns surrounding this trend revolve around cultural appropriation, exploitation, and the misrepresentation of Indigenous identities. A particularly pressing issue is the adaptation of Dhokra bronze deity idols for global markets. Dhokra art, an ancient metal-casting technique practiced by tribal artisans in India, holds deep spiritual and historical significance. Traditionally, these artifacts are not merely decorative; they serve as sacred symbols that embody religious and cultural values passed down through generations. However, with the increasing commercialization of Indigenous art, these spiritual objects have been repurposed for mass consumption, leading to the dilution of their cultural meaning. This process not only alters the original intent behind the art but also results in the economic marginalization of Indigenous artisans, who often do not receive fair compensation for their craftsmanship. The commodification of tribal heritage raises concerns about the ethical responsibilities of designers and artists and the extent to which they should engage with Indigenous art without reinforcing historical patterns of exploitation and cultural erasure. Beyond the ethical dilemmas of appropriation and commodification, this paper also examines the broader implications of these practices concerning power dynamics and legal frameworks. Many Indigenous artists and communities lack the legal protections necessary to safeguard their cultural expressions, leaving them vulnerable to exploitation by elite designers and corporations. The absence of clear intellectual property rights for Indigenous artworks allows for unchecked use and replication without consent. Addressing these challenges requires a multidimensional approach, including the establishment of ethical guidelines that promote collaboration, informed consent, and fair compensation. Additionally, legal reforms aimed at protecting Indigenous intellectual property rights could help prevent unauthorized use of traditional art forms while ensuring that tribal communities retain agency over their cultural heritage. This study highlights the urgency of ethical considerations in the adaptation of Indigenous art and advocates for responsible practices that respect the cultural and spiritual significance of traditional artworks. By fostering a more equitable relationship between Indigenous artists and the global art and design industries, it is possible to create a framework that prioritizes cultural integrity and social justice.